EFFECT OF PARTIAL SUBSTITUTION SPIRULINA INSTEAD OF SOYBEAN MEAL IN COMMON CARP CYPRINUS CARPIO L. DIET ON SOME BLOOD PICTURE AND SOME BIOCHEMICAL CRITERIA - & Bashi, Mohammad (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study conducted to find the effect of partial replacement of soybean meal by Spirulina Arthospira platensis on some blood picture and biochemical criteria in common carp Cyprinus carpio. Fish were fed on five experimental diets contained spirulina with ratio 1.45%, 2.90%, 3.54% and 6.10% of the total diet as well as control ( without spirulina) for 56 days . Results of the statistical analysis showed a significant decrease (p≤ 0.05) in the concentration of hemoglobin in treated fish fed on spirulina diets, meanwhile a significantly differences (p≤0.05) for stress index and the albumin criteria for fish fed at fifth diet comparing with control diet. The aspartate amino transferase for fish fed on the control diet increased significantly (p≤ 0.05) compared for other experimental diets. The results of the current study show that replacing the soybean meal with spirulina by 11.8 % (3.54 of the total diet) improved the studied criteria compared to the control diet.